Structure–Activity Relationship Studies of Functionally Selective Kappa Opioid Receptor Agonists that Modulate ERK 1/2 Phosphorylation While Preserving G Protein Over βArrestin2 Signaling Bias - Lovell, Kimberly M. (ACS Chem Neurosci, 2015)
Kappa opioid receptor (KOR) modulation is a promising target for drug discovery efforts due to KOR involvement in pain, depression, and addiction behaviors. We recently reported a new class of triazole KOR agonists that displays significant bias toward G protein signaling over βarrestin2 recruitment; interestingly, these compounds also induce less activation of ERK1/2 map kinases than the balanced agonist, U69,593. We have identified structure–activity relationships around the triazole scaffold that allows for decreasing the bias for G protein signaling over ERK1/2 activation while maintaining the bias for G protein signaling over βarrestin2 recruitment. The development of novel compounds, with different downstream signaling outcomes, independent of G protein/βarrestin2 bias, provides a more diverse pharmacological toolset for use in defining complex KOR signaling and elucidating the significance of KOR-mediated signaling.